2016
DOI: 10.1007/s13277-016-4880-x
|View full text |Cite|
|
Sign up to set email alerts
|

ΔNp63 regulates cell proliferation, differentiation, adhesion, and migration in the BL2 subtype of basal-like breast cancer

Abstract: Triple-negative breast cancers (TNBC) comprise a heterogeneous subgroup of tumors with a generally poor prognosis. Subclassification of TNBC based on genomic analyses shows that basal-like TNBCs, specifically the basal A or BL2 subtype, are characterized by the expression of ΔNp63, a transcription factor that has been attributed a variety of roles in the regulation of proliferation, differentiation, and cell survival. To investigate the role(s) of p63 in basal-like breast cancers, we used HCC1806 cells that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The major findings from this model were related to alterations of differentiation markers, where p63 is required to suppress expression of luminal markers and maintain the basal epithelial phenotype, but p63 loss is insufficient to induce full luminal-type differentiation. We also found that p63 depletion changed expression of adhesion molecules in a similar manner to that observed here, with reciprocal changes in FAT2 , ITGA2 , CLDN1 , LAMA4 and CEACAM6 following p63 depletion [ 29 ] or p63 induction (this manuscript). However, either over-expression or gene knockout each caused a loss of cellular adhesion in the respective cell lines, indicating that the consequences of manipulating p63 levels are dependent on the cells under investigation, which likely relates to their dependence on p63 and their different genetic backgrounds.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The major findings from this model were related to alterations of differentiation markers, where p63 is required to suppress expression of luminal markers and maintain the basal epithelial phenotype, but p63 loss is insufficient to induce full luminal-type differentiation. We also found that p63 depletion changed expression of adhesion molecules in a similar manner to that observed here, with reciprocal changes in FAT2 , ITGA2 , CLDN1 , LAMA4 and CEACAM6 following p63 depletion [ 29 ] or p63 induction (this manuscript). However, either over-expression or gene knockout each caused a loss of cellular adhesion in the respective cell lines, indicating that the consequences of manipulating p63 levels are dependent on the cells under investigation, which likely relates to their dependence on p63 and their different genetic backgrounds.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with this notion, ΔNp63 promotes normal mammary stem cell activity by enhancement of Wnt signalling and through this mechanism governs tumour-initiating activity of basal-like breast cancer [ 28 ]. In general agreement with these findings, abrogation of endogenous ΔNp63 causes a switch towards luminal phenotype and away from the basal phenotype in basal breast cancer cells, indicating a role in lineage regulation, although p63 silencing was insufficient to cause full luminal-type differentiation [ 29 ]. Further, ΔNp63 acts as a survival factor in a subset of breast cancers by antagonizing p73-mediated apoptosis [ 23 ].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The same mechanisms occur for p73 and p63: p73 displays 14 isoforms and p63 exhibits 10 isoforms ( 59 , 90 , 109 117 ) (Figure 1 ). The N-terminal truncated isoforms ΔNp73 and ΔNp63 are highly expressed in the development and display an oncogenic dominant-negative function to p73 and p63 full-length (TAp73 and TAp63, respectively) and wt-p53 ( 39 , 114 , 118 124 ).…”
Section: Protein Structure and Respective Isoforms Of The P53 Family mentioning
confidence: 99%
“…The knockout efficiency was confirmed in the bulk populations via immunoblotting. sgRNA target sequences were selected from Brunello library (29) and Orzol and colleagues (30). Nontarget sgRNAs from the Gecko library v2 (31) were used as scramble sgRNAs.…”
Section: Crispr-cas9 Genome Editingmentioning
confidence: 99%